2017
DOI: 10.1021/acssuschemeng.7b00846
|View full text |Cite
|
Sign up to set email alerts
|

Methane Hydrate Formation Promoted by −SO3-coated Graphene Oxide Nanosheets

Abstract: Sodium dodecyl sulfate (SDS) has been reported as the most efficient kinetic promoter for hydrate-based natural gas storage and transportation; however, the foam generation during hydrate dissociation is a serious problem. In this work, we grafted the −SO 3 − group (similar as the hydrophilic group of SDS) on nanosheets of graphene oxide (GO) to prepare −SO 3 −-coated GO nanosheets (sulfonate graphene oxide, SGO), which were then used to promote methane hydrate formation. For comparison, graphene (GP) and GO w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 30 publications
(52 reference statements)
0
63
0
Order By: Relevance
“…These enhancements might be attributable to the increase in initial dissolved gas in nanofluid, heterogeneous nucleation, and the heat transfer coefficient. Wang et al (2017) used graphene nanofluid to promote methane hydrate formation at initial conditions of 6 MPa and 277.15 K with 300 rpm stirring and found that graphene (0.25-0.75 g L −1 ) reduced the hydrate formation period by 45-80% and improved the hydrate formation rate and the storage capacity by 190-660% and 45-70%, respectively, compared with pure water. The results implied that the graphene nanosheets not only increased heterogeneous nucleation in the system and provided abundant active sites for hydrate nucleation but also produced a high transfer efficiency that could remove the heat generated by hydrate formation from the system, consequently improving the efficiency of methane hydrate formation.…”
Section: Graphenementioning
confidence: 99%
See 1 more Smart Citation
“…These enhancements might be attributable to the increase in initial dissolved gas in nanofluid, heterogeneous nucleation, and the heat transfer coefficient. Wang et al (2017) used graphene nanofluid to promote methane hydrate formation at initial conditions of 6 MPa and 277.15 K with 300 rpm stirring and found that graphene (0.25-0.75 g L −1 ) reduced the hydrate formation period by 45-80% and improved the hydrate formation rate and the storage capacity by 190-660% and 45-70%, respectively, compared with pure water. The results implied that the graphene nanosheets not only increased heterogeneous nucleation in the system and provided abundant active sites for hydrate nucleation but also produced a high transfer efficiency that could remove the heat generated by hydrate formation from the system, consequently improving the efficiency of methane hydrate formation.…”
Section: Graphenementioning
confidence: 99%
“…As a novel carbon nanostructure, graphene presents excellent mechanical strength and thermal conductivity and large specific surface area, making it a promising candidate for the promotion of gas hydrate formation (Wang et al, 2017). Here, we implement a review focusing on graphene-based promoters of gas hydrate formation.…”
Section: Introductionmentioning
confidence: 99%
“…Since graphene has smooth surfaces and is easy to functionalize by sulfonate groups or to load with metal nanoparticles, this two-dimensional carbon material is also introduced to hydrate formation reactions. Wang et al (2017) grafted sulfonate groups successfully to graphene by covalent bonding and used it in methane hydrate formation. The results showed that the promotion efficiency of SGO (sulfated graphene) was better than that of GO (oxidized graphene).…”
Section: Gas Hydrate Formation With Carbon-based Nanofluidmentioning
confidence: 99%
“…Another review conducted by Nashed et al (2018) shed light on the nanomaterials for gas hydrate formation, where various metal-based particles, like nano-Ag, Cu, CuO, and ZnO were discussed, and it was concluded that nanoparticles not only could help to promote mass transfer but they could also contribute to heat transfer enhancement in the hydrate reaction. Additionally, some non-metal materials such as silica nanoparticles (Wang et al, 2019), graphene (Wang et al, 2017), and carbon nanotubes (Pasieka et al, 2014) exhibited excellent performance in promoting gas storage capacities and hydrate formation rate.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to surfactants, other substances, such as graphene and its derivatives [48][49][50] , nanoparticles (iron(II,III) oxide (Fe3O4) [36; 51] and cupric oxide (CuO) [35] ) with a surfactant to suspend in water, have also been investigated.…”
Section: Additivesmentioning
confidence: 99%